Against theoretical evangelism: Imagining the possibilities of a critical approach to theorising in professional academic development - Naidoo, K. (South African Journal of Higher Education, 2016)
This article contributes to dialogue on theorising in higher education, with particular reference to professional academic development. It provides a critique of the evangelical adherence to dominant theories and argues that their uncritical use cannot contribute to addressing social injustices in higher education. It also argues for theorisation in professional academic development that is more sensitive to context. Drawing on insights from C. Wright Mills (2000), the article suggests that, by viewing theorisation through the lens of a sociological imagination, it is possible to engage critically with dominant discourses and come up with creative solutions that are aligned with a viewpoint that promotes social justice in professional academic development, as well as addressing social inequities and injustices in higher education.